2013
DOI: 10.1371/journal.pone.0059083
|View full text |Cite|
|
Sign up to set email alerts
|

Fibroblast Growth Factor 2 Induces E-Cadherin Down-Regulation via PI3K/Akt/mTOR and MAPK/ERK Signaling in Ovarian Cancer Cells

Abstract: Fibroblast growth factor 2 (FGF2) is produced by ovarian cancer cells and it has been suggested to play an important role in tumor progression. In this study, we report that FGF2 treatment down-regulated E-cadherin by up-regulating its transcriptional repressors, Slug and ZEB1, in human ovarian cancer cells. The pharmacological inhibition of phosphatidylinositol-3-kinase (PI3K), mammalian target of rapamycin (mTOR), and MEK suggests that both PI3K/Akt/mTOR and MAPK/ERK signaling are required for FGF2-induced E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 64 publications
(91 reference statements)
5
52
0
Order By: Relevance
“…This strongly suggests that corneal endothelial cells behave differently ex vivo versus in vitro. Moreover, suppression of E-cadherin expression by FGF2 treatment in corneal endothelial cells also supports conversion to a mesenchymal phenotype and is consistent with previous reports showing similar results in ovarian cancer cells (34,36).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This strongly suggests that corneal endothelial cells behave differently ex vivo versus in vitro. Moreover, suppression of E-cadherin expression by FGF2 treatment in corneal endothelial cells also supports conversion to a mesenchymal phenotype and is consistent with previous reports showing similar results in ovarian cancer cells (34,36).…”
Section: Discussionsupporting
confidence: 92%
“…Another key inducer of mesenchymal transition is FGF2 (34)(35)(36), and SNAI1 has been reported to be a downstream target of FGF2, during chondrogenesis and in certain forms of achondroplasia (37). We previously reported that FGF2 signals through PI 3-kinase to induce mesenchymal transition in rabbit and human CEC.…”
mentioning
confidence: 97%
“…Ras/ERK1/2 activation seems to be a necessary step in the induction of EMT (22,42,48). Also, it is reported that ERK1/2 and/or Akt is an important mechanism in EMT induced by various mediators such as TGF-␤, EGF, and FGF-2 (27,48). Our study demonstrated that kindlin-2 induced tubular EMT through Ras/ERK1/2 and Ras/Akt pathways.…”
Section: Discussionsupporting
confidence: 62%
“…EMT is a reversible process, whereby the epithelial cells lose their junctions and polarity, reorganize their cytoskeleton, gain ability of motility, transit into mesenchymal cells and develop an invasive phenotype (30). The functional loss of E-cadherin is the typical characteristic of EMT and this contributes to the destabilization of adheren junctions, as well as tumor invasion and metastasis (20,30,47,48). Therefore, SFN is capable of suppressing the process of EMT by inducing E-cadherin.…”
Section: Discussionmentioning
confidence: 99%